THE MAIN CHARACTERISTICS OF MARKET AND MARKETING OF ORGANIC AGRICULTURE PRODUCTS - Branislav Vlahović; Maja Štrbac (Ekonomika Poljoprivrede (1979), 2007)
About 70 years ago, machines and chemistry played an important role for human beings. That was the realization of harmonious life between man and machine. Now, the theme is realization of harmonious life between man and environment. We can witness irregularities regarding proper nourishment of population which affects the health and well-being of people in the world. Highly developed countries have problems in the area of rational consumption and health safety of food.